Caesar As God's Banker: Using Germany's Church Tax As an Example of Non-Geographically Bounded Taxing Jurisdiction - Stephanie Hoffer (Washington University Global Studies Law Review, 2010)
This Article compares the modern-day German church tax to church taxes levied by the American colonies and early states and concludes that, unlike its American counterparts, the German church tax is not wholly a "church" tax.
Keywords: Religious institutions -- Taxation; Catholic Church -- Germany; Catholic Church -- United States; Church buildings; Local taxation